Mix design of palm oil fiber concrete - Ahmad, Mohd Hilton (2008)
Nowadays, most countries are looking forwards in reducing POLLUTION; one of the best solutions is utilizing waste product into recycle materials. This not only can develop sustainable environment management but also introducing new materials for public usage. As Malaysia currently heading to biotechnology hub in the region, it is expected that billions tones of palm oil by-products will be produced annually and normally been treated as waste disposal. This paper discussed the usage of palm oil fiber can be used as discrete reinforcing fiber that can restrain minor cracks that developed in the concrete from spreading. Fiber reinforced concrete is able to increase its performance against tensile strength and toughness due to ability to adsorb energy by reinforcing fibers. Palm oil fiber concrete was investigated for its workability, compressive strength and tensile splitting strength where trial mixture based on Department of Environmental (DOE) was conducted. mix designs according to fibres added and PFA replacement level were identified and tested for slump, compression and tensile spliiting tests. Study shows that the mix design of Palm oil Fiber concrete added with and 0.50 and 10% PFA replacement gave the best compresive strength. It is shows that series with using palm oil fibres reduces workability and compressive strength but increse the tensile splitting strength.